An AGIL-Based Transition Program for Islamic Elementary School Entry - Siti Liani,; Maemonah,; Sintha Sih Dewanti,; Barsihanor,; Galuh Nashrulloh KMR,; Wan Suraya, (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2025)
Objectives: The importance of transition programs for primary school entry globally (not just in Indonesia). Method: A qualitative approach with a descriptive case study design was employed. The research subjects consisted of school principals, early childhood and primary school teachers, and parents from two educational institutions in South Kalimantan, Indonesia. Data were collected through observation, interviews, and documentation, and analyzed using Miles and Huberman’s model. Results: The research findings indicate that the Early Childhood Education -Primary School transition program generally changes the perceptions and practices of teachers and parents, shifting the focus from early academic achievement to the holistic development of children, including social-emotional and character aspects. Theoretical Contribution: This strengthens the theory of Islamic education, which emphasizes a balance between the spiritual, social, and intellectual aspects of learners. The AGIL approach becomes a relevant conceptual framework to understand how Islamic educational institutions can function systemically. Implication: The program successfully builds better collaboration among stakeholders and strengthens parental involvement, thereby contributing to structural and cultural transformations in the early childhood education system and supporting children’s readiness to enter formal education.